Pengaruh Kredibilitas Influencer Beby Tsabina pada Media Sosial Instagram dan Keselarasan Diri terhadap Sikap Influencer Serta Dampaknya pada Niat Konsumen terhadap Produk Barenbliss - Dessy Herdiana; Desi Jaelani; Reminta Lumban Batu (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the role of influencer credibility Beby Tsabina in shaping consumer attitudes and behavioral intentions towards Barenbliss products through Instagram social media. Background Problems: How do influencer credibility, Instagram social media, and self-congruence influence attitudes towards influencers and their impact on consumer behavioral intentions towards Barenbliss products. Novelty: This study combines three main variables of influencer credibility, Instagram social media, and self-congruence which are simultaneously analyzed towards consumer attitudes and intentions, especially in the local Indonesian context with a specific influencer figure, namely Beby Tsabina. Research Methods: The method used is a quantitative approach with a survey technique on Instagram users who know Beby Tsabina and Barenbliss products. Data were analyzed using Structural Equation Modeling (SEM) techniques. Finding/Results: The results show that influencer credibility, Instagram social media, and self-congruence have a significant positive effect on attitudes towards influencers, which in turn influence consumer behavioral intentions. Conclusion: The conclusion of this study is that credibility and congruence between influencers and consumers play a very important role in shaping purchase intentions through positive attitudes towards influencers.